The Contribution Of Facility Management And Service Quality To Soccer Performance - Eka Abdurrahman; Lubis, Ade Evriansyah (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2024)
The purpose of this study was to determine the contribution of facility management and service quality to soccer sports achievement in the Physical Education, Health, and Recreation Study Program, Sekolah Tinggi Olahraga dan Kesehatan Bina Guna. The research method used is quantitative research. In this study, the object of research is facility management (X1) quality of education services (X2) and sports achievement (Y). The research population was students of the Physical Education, Health, and Recreation Study Program at Sekolah Tinggi Olahraga dan Kesehatan Bina Guna with a total population of 550 students. The sample in this study were 85 people. The data collected are in the form of numbers, written information, oral information and various facts related to the focus of the research obtained through the instrument of distributing questionnaires to 55 students who were used as research samples in the Physical Education, Health, and Recreation Study Program of Sekolah Tinggi Olahraga dan Kesehatan Bina Guna. After processing and analyzing the data, the results obtained are the contribution between facility management and sports achievement and the contribution between service quality and sports achievement. This means that the better the facility management and service quality, the sports achievement will increase.